Liraglutide and a lipidized analog of prolactin-releasing peptide show neuroprotective effects in a mouse model of β-amyloid pathology - Holubová, Martina; Hrubá, Lucie; Popelová, Andrea; Bencze, Michal; Pražienková, Veronika; Gengler, Simon; Kratochvílová, Helena; Haluzík, Martin; Železná, Blanka; Kuneš, Jaroslav; Hölscher, Christian; Maletínská, Lenka (Neuropharmacology, 2019)
Obesity and type 2 diabetes mellitus (T2DM) are important risk factors for Alzheimer's disease (AD). Drugs originally developed for T2DM treatment, e.g., analog of glucagon-like peptide 1 liraglutide, have shown neuroprotective effects in mouse models of AD. We previously examined the neuroprotective properties of palm11-PrRP31, an anorexigenic and glucose-lowering analog of prolactin-releasing peptide, in a mouse model of AD-like Tau pathology, THY-Tau22 mice. Here, we demonstrate the neuroprotective effects of palm11-PrRP31 in double transgenic APP/PS1 mice, a model of AD-like β-amyloid (Aβ) pathology. The 7-8-month-old APP/PS1 male mice were subcutaneously injected with liraglutide or palm11-PrRP31 for 2 months. Both the liraglutide and palm11-PrRP31 treatments reduced the Aβ plaque load in the hippocampus. Palm11-PrRP31 also significantly reduced hippocampal microgliosis, consistent with our observations of a reduced Aβ plaque load, and reduced cortical astrocytosis, similar to the treatment with liraglutide. Palm11-PrRP31 also tended to increase neurogenesis, as indicated by the number of doublecortin-positive cells in the hippocampus. After the treatment with both anorexigenic compounds, we observed a significant decrease in Tau phosphorylation at Thr231, one of the first epitopes phosphorylated in AD. This effect was probably caused by elevated activity of protein phosphatase 2A subunit C, the main Tau phosphatase. Both liraglutide and palm11-PrRP31 reduced the levels of caspase 3, which has multiple roles in the pathogenesis of AD. Palm11-PrRP31 increased protein levels of the pre-synaptic marker synaptophysin, suggesting that palm11-PrRP31 might help preserve synapses. These results indicate that palm11-PrRP31 has promising potential for the treatment of neurodegenerative diseases.
Keywords: Animals; myši transgenní; Neurogenesis; zánět; hipokampus; Amyloid beta-Peptides; tau Proteins; Gliosis; Mice, Transgenic; neurogeneze; lidé; amyloidní beta-protein; Prolactin-Releasing Hormone; Inflammation; Humans; liraglutid; amyloidóza; Male; myši inbrední C57BL; modely nemocí na zvířatech; amyloidní plaky; Amyloidosis; Neuroprotective Agents; Alzheimer Disease; Plaque, Amyloid; Disease Models, Animal; Liraglutide; Alzheimerova nemoc; Hippocampus; Random Allocation; zvířata; mužské pohlaví; Mice, Inbred C57BL; glióza; proteiny tau; náhodné rozdělení; hormon uvolňující prolaktin; neuroprotektivní látky